Sarawak Foundation (Yayasan Sarawak) / Lya Liziana Sapwan - Sapwan, Lya Liziana (University Technology MARA Sarawak, 2018)
Sarawak Foundation or Yayasan Sarawak was established through the Sarawak Foundation Ordinance by the Sarawak State Government on 27 May 1971 under the leadership of Datuk Patinggi Haji Abdul Rahman Ya'kub. the Chief Minister of Sarawak at that time. He aimed to improve the standard of education amongst the people of Sarawak, and became the first Chairman ofthe Sarawak Foundation. Datuk Amar Abang Haji Yusuf Puteh, the State Secretary at that time, was appointed as the secretary to the Sarawak Foundation. Main location of Sarawak Foundation building is located at Jalan Sultan Tengah, Petra Jaya. There are also another two branches of Sarawak Foundation located at Persiaran Ampang, Kuala Lumpur and Brondesbury Park, London.